Efficacy of Homeopathic Medicines to treat Covid-19 diseases - Islam, Md Mazharul; Chowdhury, Ashru kana; Ismail, Russtum Mohammad; Nargis, Aklima (Indian Journal of Integrative Medicine, 2022)
Among the seven human coronaviruses (HCoVs), SARS, MERS, and SARS-CoV2 caused the most severe illnesses. Although WHO recommended three vaccines against Covid-19, this does not guarantee complete protection against the human body. Since the virus constantly changes and infects people causing great suffering and death, we must protect ourselves by following specific hygiene rules. This study showed the effectiveness of Homeopathic Remedies as the alternative treatment for Covid-19. Samples (suspected and confirmed patients of Covid-19) were given homeopathic medicines, and the results were recorded. This study aims to demonstrate a global effort to control the coronavirus (COVID-19) through alternative therapies. National health systems should promptly endorse the efficacy of validated homeopathic treatments to treat the Covid-19 disease as alternative medicine.